1983
DOI: 10.1111/j.1365-2621.1983.tb05082.x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of TBA Methods for Determination of Lipid Oxidation in Red Meat from Four Species

Abstract: Four methods of TBA analysis were used to study lipid oxidation in cooked longissimus and biceps femoris muscle from 10 antelope, deer, elk and beef animals. Pigment characteristics and total lipid were also evaluated to determine their effect on lipid oxidation. Differences (P < 0.05) existed among species for all TBA methods studied. Differences in pigmentation, percent lipid and phospholipids existed (P < 0.05) among methods of TBA analysis and among species. No one factor was consistently correlated with d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

1991
1991
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 19 publications
0
7
0
1
Order By: Relevance
“…Williams et al (1983) demonstrated that 100 g muscle tissue of antelope (960.9 mg), deer (967.4 mg) and elk (707.5 mg) had much higher phospholipid concentrations than beef (502.3 mg). The ferric haem ion acts as a catalyst of lipid oxidation.…”
Section: Discussionmentioning
confidence: 99%
“…Williams et al (1983) demonstrated that 100 g muscle tissue of antelope (960.9 mg), deer (967.4 mg) and elk (707.5 mg) had much higher phospholipid concentrations than beef (502.3 mg). The ferric haem ion acts as a catalyst of lipid oxidation.…”
Section: Discussionmentioning
confidence: 99%
“…Williams et al (1983) reported the phospholipid concentrations in various meat species and noted that meat from antelope (960.9 mg/100 g), deer (967.4 mg/100 g) and elk (707.5 mg/100 g) had much higher phospholipid concentrations than beef (502.3 mg/100 g). The higher PUFA concentrations observed in venison/wild game could contribute to the rapid discoloration in post-mortem muscles (Stevenson-Barry et al, 1999).…”
Section: Lipid Oxidationmentioning
confidence: 99%
“…These authors suggested that EM should only be used if compounds producing the yellow pigment are absent, or present in sufficiently small quantities not to interfere. The EM may be also inadequate in cases of coloured samples and for high fat samples (>10%) where turbidity may occur in extracted samples (Hoyland & Taylor, 1991;Salih et al, 1987;Siu & Draper, 1978;Williams et al, 1983). Some authors (Draper et al, 1993; have reported that these interfering compounds can be successfully removed by filtering the extract by solid-phase extraction (C 18 cartridges).…”
Section: Tba-mda Adductmentioning
confidence: 99%
“…Nowadays, numerous protocols and modifications of this method have been reported in the literature. Four basic approaches have been employed to conduct the TBA test on food samples: (i) application of direct heating on the food samples with a TBA solution and extracting the resulting TBA-MDA adduct with butanol (Tarladgis et al, 1964;Williams, Field, Miller, & Welke, 1983), (ii) MDA determination on the extracted lipid portion of food samples (Pikul, Leszczynski, & Kummerow, 1983, (iii) MDA determination on aqueous acid extracts of food samples (Pikul et al, 1983;Salih, Smith, Price, & Dawson, 1987;Tarladgis et al, 1964), and (iv) MDA determination on a portion of the steam distillate from food samples (Hoyland & Taylor, 1989;Ke, Cervantes, & Robles-Martinez, 1984;Tarladgis, Watts, Younathan, & Dugan, 1960). The two latter -the aqueous acid extraction method (EM) and the distilation method (DM) -are generally the most popular TBA tests amongst meat researchers (Estévez, Morcuende, & Ventanas, 2009).…”
Section: Introductionmentioning
confidence: 99%